The effects of a multisite aerobic exercise intervention on asthma morbidity in sedentary adults with asthma: the Ex-asthma study randomised controlled trial protocol. Issue 6 (19th June 2013) - Bacon, Simon L; Lavoie, Kim L; Bourbeau, Jean; Ernst, Pierre; Maghni, Karim; Gautrin, Denyse; Labrecque, Manon; Pepin, Veronique; Pedersen, Bente Klarlund
Abstract : Objective: Aerobic exercise can improve cardiovascular fitness and does not seem to be detrimental to patients with asthma, though its role in changing asthma control and inflammatory profiles is unclear. The main hypothesis of the current randomised controlled trial is that aerobic exercise will be superior to usual care in improving asthma control. Key secondary outcomes are asthma quality of life and inflammatory profiles. Design: A total of 104 sedentary adults with physician-diagnosed asthma will be recruited. Eligible participants will undergo a series of baseline assessments including: the asthma control questionnaire; the asthma quality-of-life questionnaire and the inflammatory profile (assessed from both the blood and sputum samples). On completion of the assessments, participants will be randomised (1:1 allocation) to either 12-weeks of usual care or usual care plus aerobic exercise. Aerobic exercise will consist of three supervised training sessions per week. Each session will consist of taking a short-acting bronchodilator, 10 min of warm-up, 40 min of aerobic exercise (50–75% of heart rate reserve for weeks 1–4, then 70–85% for weeks 5–12) and a 10 min cool-down. Within 1 week of completion, participants will be reassessed (same battery as at baseline). Analyses will assess the difference between the two intervention arms on postintervention levels of asthma control, quality of life and inflammation, adjusting for age, baseline inhaled corticosteroid prescription, body weight change and pretreatment dependent variable level. Missing data will be handled using standard multiple imputation techniques. Ethics and dissemination: The study has been approved by all relevant research ethics boards. Written consent will be obtained from all participants who will be able to withdraw at any time. Results: The result will be disseminated to three groups of stakeholder groups: (1) the scientific and professional community; (2) the research participants and (3) the general public. Registration Details ClinicalTrials.gov Identifier: NCT00953342